Urinary Neutrophil Gelatinase-Associated Lipocalin and Its Association with the Histological Pattern in Idiopathic Nephrotic Syndrome (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Idiopathic nephrotic syndrome (INS) is the most common glomerular disorder of childhood. Clinical outcome of children with nephrotic syndrome depends on underlying histopathlogy and responsiveness to steroid treatment. Minimal change disease (MCD) has a favorable long-term prognosis whereas, other than minimal change nephrotic syndrome is often resistant to steroid and is more likely to progress to end-stage renal disease (ESRD). Neutrophil gelatinase-associated lipocalin (NGAL) which is a small protein belonging to the lipocalin superfamily has been demonstrated to be a powerful risk marker of chronic kidney disease progression. This study was undertaken to determine whether urinary NGAL could be used as a biomarker in differentiating minimal change disease from other glomerular histologic lesions in idiopathic nephrotic syndrome in children.Objectives: To evaluate the association between urinary NGAL and histological pattern in idiopathic nephrotic syndrome.Materials and Methods: This cross-sectional, multicenter study was conducted in the Department of Paediatric Nephrology, Dhaka Shishu Hospital and Department of Paediatric Nephrology, Bangabandhu Sheikh Mujib Medical University from June 2014 to May 2015. Fifty-one children with idiopathic nephrotic syndrome comprising 12 children with minimal change disease (MCD) and 39 with other than minimal change nephrotic syndrome were included. Urinary NGAL was measured using a commercially available HUMAN NGAL/ LIPOCALIN 2 ELISA kit which employed the quantitative sandwich enzyme immunoassay technique. Median urinary NGAL level were compared between MCD and other than MCD. Median urinary NGAL and urinary creatinine ratio also compared between two groups. The prognostic accuracy of urinary NGAL was assessed by receiver operating characteristic (ROC) curve analysis.Results: Median urinary NGAL (uNGAL) level of MCD group was 44.5 [IQR: 32-109.5] (ng/ml) and that of the other than MCD group was 130 [IQR:85-172] (ng/ml). This difference was statistically significant (p=0.004). Median urine NGAL and urine creatinine ratio was significant between two groups (MCD=105.5 ng/mg and other than MCD=288 ng/mg, p-value was